MENGULAS NILAI AMR AL- MA’RŪF NAHYI AL MUNKAR PADA PROGRAM PEMBERDAYAAN MASYARAKAT: Studi Kasus Pada Lembaga Kelompok Informasi Masyarakat - Efitrianisa, Siti Nur (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2017)
The purpose of this study is to reveal the value of al-amar al-ma'rūf wa an-nahyi al-munkar. This study applies the case study method through a qualitative approach. Based on the results of the studies in this paper, it shows that the community empowerment program carried out by KIM contains the value of al-amar al-ma'rf wa an-nahyi al-munkar, it can be seen from the aspect of al-amar al-ma'ruf through calling on the public to utilize technology and improve economic levels through programs provided by KIM. The an-nahyi al-munkar aspect can be seen from the call for the ban on KIM to the public to stay away from false information. Keywords: KIM, al-amar al-ma'rūf wa an-nahyi al-munkar, Community Empowerment